Knowledge and preventive practices of malaria among pregnant women in Huye district Southern province, Rwanda - Habimana, Amos; Gikunju, Joseph; Magu, Dennis (International Journal Of Community Medicine And Public Health, 2020)
Background: Regardless of the accessibility of effective malaria control interventions, malaria has been reported in first place with a 25% morbidity rate in Rwanda, particularly in pregnancy. This study explored knowledge and preventive practices of malaria among pregnant women in Huye district Southern province, Rwanda. Methods: Study design was cross-sectional descriptive, 384 pregnant women living in Tumba sector were recruited. A semi-structured questionnaire was used for data collection, and data were entered in SPSS version 21 for analysis and the Chi-square test was computed for measuring the associations between variables at 5% level of statistical significance. Results: Of the 384 respondents, 340 (88.5%) were married and the mean age was 29.5±6.8 years with 172 (44.8%) aged between 25 and 29 years. Majority 224 (58.4%) had primary level of education and 147 (27.9%) were agricultures. 96 (25%) of respondents had low knowledge whereas 42 (10.9%) had high knowledge and 246 (64.1%) moderate knowledge. 298 (77.6%) were aware and knew that malaria is transmitted by female anopheles and the majority of respondents 323 (84.1%) were using LLINs. Education level, marital status, occupation were associated with malaria knowledge on preventive practices and LLINs utilization (p=0.001). Conclusions: This study revealed satisfactory knowledge of malaria prevention among pregnant women in southern Rwanda despite the poor implementation of current malaria control strategies. There is a need for sustaining and expanding the current LLINs ownership and utilization level and also improving public health education on malaria knowledge, preventive practices, and high health risks behaviors for malaria control and elimination.